Postprandial plasma 5-hydroxytryptamine in diarrhoea predominant irritable bowel syndrome: a pilot study. Issue 1 (1st January 1998) - Bearcroft, C P; Perrett, D; Farthing, M J G
Abstract : Background —Increased concentrations of 5-hydroxytryptamine (5-HT) can be detected in the systemic circulation after a meal and may be involved in the physiological control of gastrointestinal motility. Abnormalities of 5-HT release after a meal might explain some of the postprandial symptoms associated with the irritable bowel syndrome (IBS). Aim —To investigate the effect of a standard meal on plasma 5-HT and urinary 5-hydroxyindole acetic acid (5-HIAA) concentrations in patients with diarrhoea predominant IBS and in healthy volunteers. Methods —After an overnight fast, six volunteers and five patients with IBS were given a carbohydrate-rich meal. Blood and urine samples were taken before and for four hours after the meal. Platelet-poor plasma 5-HT and urinary 5-HIAA were analysed by reversed phase high performance liquid chromatography with fluorometric detection. 5-HIAA was expressed as a ratio with urinary creatinine concentration, which was measured by spectrophotometry. Results —During the four hour postprandial period, 5-HT concentrations were significantly higher in patients with IBS than in healthy volunteers at 0.5 hours (p<0.05), 2 hours (p<0.05) and 2.5 hours (p<0.05). 5-HT was not detected in the plasma in the fasting state in patients or volunteers. Median peak 5-HT in patients with IBS (359 (198–796) nmol/l) was significantly greater than volunteers (83 (7–190)) (p<0.05). "Area under the curve" for 5-HT detection was greater for patients with IBS (317 (138–771)) than for healthy volunteers (51 (4–129); p<0.05).The duration of the 5-HT peak was significantly longer in patients with IBS (3 (1–3) hours) than in the healthy volunteers (1 (1–1) hours; p<0.01). Postprandial urinary median 5-HIAA values in controls (5.6 (5.5–5.8) μmol/mmol creatinine) and patients with IBS (3.0 (2.5–6.8) μmol/mmol creatinine) were not significantly different from preprandial values (controls: 5.9 (5.5–6.6) μmol/mmol creatinine; patients with IBS: (6.2 (2.4–9.3) μmol/mmol creatinine). Conclusion —These findings indicate that there may be a difference in the way that 5-HT is released in patients with diarrhoea predominant IBS, and could suggest a possible role for 5-HT in the postprandial symptoms of these patients.